IMPLEMENTASI KEBIJAKAN PHBM DI KPH BLORA : WAJAH BARU DOMINASI PENGELOLAAN HUTAN - , ENDAH ARUM PRATIWI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study is about the implementation of CBFM policy in Forest Lap United (FLU) of Blora. It's been 12 years this implementation is executed but not yet to show results. Therefore, the results of the implementation needs to be revisited to restore the contents of the policy and see policy context. In the theory, it says that the policy is the result of the domination of the interests of policy holders. In policy domination there is always a subject of policy and policy objects. Perhutani is a major subject in forest management in Java. In 2001, the Perhutani issued CBFM policy whose spirits are share and invite many actors. This policy is basically trying to be the bridge to the open access forest villagers (FV) entered into forest management. The study was to see if the centralized management style of Perhutani and of course dominance is still involved in the implementation of CBFM policy. Perhutani then develop instruments of domination to secure its interests. The process of dominance had begun when any policy making to implementation of this dominance is still enveloped. There are three points in domination Perhutani, the interests of domination, domination of the land, and the dominance of institutions. All three make a groove dominance following the instructions of Perhutani. At the end, the dominance doesnât bring the forest villagers to prosperity and forest sustainability as a policy goal. Forest village communities have limited space to articulate their interests. Dominance creates dependency because Perhutani is full of power over the public land utilized. Forest management is still using the same style despite the intention to change themselves. Dominance persists in the spirit of sharing policies slogan.